Glass factory found: Basinwide (600 km) preservation of sponges on the Phosphoria glass ramp, Permian, USA - Zackery Wistort; Leif Tapanila; William Moynihan; Kathleen Ritterbush (PLoS ONE, 2025)
A new analysis of misdiagnosed fossil deposits contextualizes the geologic origin for one of North America’s most valuable, but enigmatic, sedimentary units: the Phosphoria Rock Complex (Permian). We describe extensive and repeated deposits of in situ marine sponge fossils, previously interpreted as silicified trace fossils, which crop out today as mountain cliffs and widespread landmarks in Nevada, Utah, Idaho, Wyoming, and Montana. Moreover, we propose that the detritus from these organisms dominated the supply of contemporaneous biosiliceous sedimentation, fueling the production of spiculite deposits throughout the northeastern Panthalassic Ocean coast. We propose that the establishment and preservation of these in situ sponge meadows were controlled by bottom-water oxygenation and by hydrodynamic energy, respectively. We present evidence that sponges possibly demonstrated a partially infaunal life habit, leading to their misdiagnosis as trace fossils. These sponge body fossils frame the Phosphoria Rock Complex’s transition from a starved, highly-concentrated phosphorite to a prolific glass ramp: an animal-mediated accumulation of opaline silica.